2002
DOI: 10.1089/089771502760342009
|View full text |Cite
|
Sign up to set email alerts
|

Severe Cerebral Blood Flow Reduction Inhibits Nitric Oxide Synthesis

Abstract: The purpose of this study was to investigate the relationship between cerebral blood flow (CBF) and nitric oxide (NO) synthesis using a rat model of transient forebrain ischemia of varying severity. Forebrain ischemia was induced for 30 min by occlusion of the bilateral common carotid arteries without hemorrhagic hypotension. The production of NO end-products (nitrite and nitrate) was measured by in vivo microdialysis, and CBF by the hydrogen clearance technique. Ischemia induced NO synthesis, although the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…However, NO concentration is transiently increased by 50% for about 30 minutes if reperfusion occurs even when iNOS has not been induced [35], [36]. A previous study suggested that NO generation during early reperfusion was mostly derived from eNOS [36]. In the present study, eNOS-specific inhibitor showed a strong inhibitory effect on cerebral vasodilation during early reperfusion, whereas nNOS-specific and iNOS-specific inhibitors only showed inhibitory effect on cerebral dilation in certain branches of the MCA.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…However, NO concentration is transiently increased by 50% for about 30 minutes if reperfusion occurs even when iNOS has not been induced [35], [36]. A previous study suggested that NO generation during early reperfusion was mostly derived from eNOS [36]. In the present study, eNOS-specific inhibitor showed a strong inhibitory effect on cerebral vasodilation during early reperfusion, whereas nNOS-specific and iNOS-specific inhibitors only showed inhibitory effect on cerebral dilation in certain branches of the MCA.…”
Section: Discussioncontrasting
confidence: 39%
“…This enhanced and prolonged NO release can be entirely ascribed to the induced expression of iNOS in response to locally produced inflammatory cytokines following ischemia with or without reperfusion [33], [34]. However, NO concentration is transiently increased by 50% for about 30 minutes if reperfusion occurs even when iNOS has not been induced [35], [36]. A previous study suggested that NO generation during early reperfusion was mostly derived from eNOS [36].…”
Section: Discussionmentioning
confidence: 97%
“…Ischemia associated with occlusion of the bilateral common carotid arteries induced increases in NO end-products (NOx) during ischemia and prominently after reperfusion, and such increases were abolished by L-NAME but only slightly reduced by 7-NI; the increase in the quantity of NO end-products became prominent and was persistent after reperfusion in rats in which the cerebral blood flow during ischemia was in the range between 22.7 and 60 ml/100 g/min, whereas in animals in which the cerebral blood flow during ischemia fell below 22.7 ml/100 g/min, the end-products decreased during ischemia increased transiently after reperfusion. (Uetsuka et al, 2002). The increase in NO seems to be derived from eNOS, and NO synthesis during and after ischemia may be related to cerebral blood flow.…”
Section: F Astrocyte-derived Nitric Oxide and Other Vasodilatorsmentioning
confidence: 99%
“…Thereafter, the brain tissue NO is reduced below detectable levels for up to 7 days (Malinski et al, 1993;Sugimura et al, 1998), indicating a long-lasting NO deficiency in the ischemic brain. If reperfusion occurs, NO concentration may transiently increase by 50% for about 30 minutes (Fassbender et al, 2000;Uetsuka et al, 2002). Concomitant with changes in NO levels, the activities of eNOS and nNOS increases within the first few minutes after MCAo, but decrease significantly thereafter (Kader et al, 1993).…”
Section: Nitric Oxide-pathophysiology In Strokementioning
confidence: 99%